Perancangan Buku Ilustrasi Bangunan Peninggalan Masa Kolonial Belanda Di Kota Medan Dalam Upaya Meningkatkan Minat Anak-Anak Terhadap Sejarah - Siregar, Nadya Ludwina; Zuhdi, Muhammad Fikri Akbar; Savitri, Elis (Syntax Corporation, 2025)
Intended to cultivate children's reading interest in the city of Medan through this illustrated book. The main focus of this book is to introduce the historical building Warenhuis, which is a silent witness to the colonial growth of the city of Medan. This design is based on the fact that there are not many visual educational media telling local stories, especially about Dutch colonial buildings, many of which are currently abandoned or damaged. The author followed five steps of the design thinking approach during the design process. This design contributes to education by using creative and educational illustration media.